A history-dependent frictional contact problem with wear for thermoviscoelastic materials - Chouchane, Lamia; Selmani, Lynda (Mathematical Modelling and Analysis, 2019)
In this manuscript we study a contact problem between a deformable viscoelastic body and a rigid foundation. Thermal effects, wear and friction between surfaces are taken into account. A variational formulation of the problem is supplied and an existence and uniqueness result is proved. The idea of the proof rested on a recent result on history-dependent quasivariational inequalities. Finally, a perturbation of the data is initiated and a convergence result is demonstrated when the perturbation parameter converges to zero.